PEMANFAATAN TEKNOLOGI PENGINDERAAN JAUH UNTUK DETEKSI KEKERINGAN PERTANIAN MENGGUNAKAN METODE NORMALIZED DIFFERENCE DROUGHT INDEX DI KABUPATEN KENDAL - Abdi Sukmono; Fadli Rahman; Bambang Darmo Yuwono (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
Drought of agricultural land is one of the most frequent disasters in Indonesia. This disaster greatly affects food security. Kendal Regency is one of the areas in Indonesia that often experience drought of agricultural land. In the year 2015 in Kendal regency there are 1055 Ha paddy field was crop failure. The threat of drought on agricultural land can be minimized if the monitoring of drought potential in a region can be known.One way that can be used for spatial drought monitoring is to use applications from remote sensing based on a particular algorithm. In the research, Normalized Difference Drought Index (NDDI) algorithm is used to distribution and extent of agricultural drought in Kendal District by 2015 using Landsat 8 satellite imagery. NDDI is the ratio between Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI).The results indicate agricultural drought using NDDI method in July 2015 with normal drought area 6980,362 ha, mild drought 13364,155 ha, moderate drought 682,847 ha and dry drought 281,81 ha. Validation results show the accuracy of the NDDI method is 82%.Â